A REVIEW OF RESEARCH PROCESS: DATA COLLECTION AND ANALYSIS - Dr. Anjana Kumari (Galaxy International Interdisciplinary Research Journal, 2022)
Research is a highly specialized activity that entails much more than simply gathering data or writing a description. It entails gathering information in a specific manner, which is then thoroughly analyzed to provide answers to research questions and evaluate results. Regardless of the subject of investigation, data collecting is at the center of any research strategy. Any research project begins with a set of questions that must be answered. Data collection is the process of carefully acquiring the desired information with the least amount of distortion possible so that the analysis can produce responses that are believable and logical. Data collection tools refer to the devices/instruments used to collect data, such as a paper questionnaire or computer-assisted interviewing system. Case Studies, Checklists, Interviews, Observation sometimes, and Surveys or Questionnaires are all tools used to collect data.